The politics of twilights: notes on the semiotics of horizon photography. Issue 4 (2nd October 2018) - Raphael, Michael W.
Abstract : Visual sociology is crucial for exploring the indexical meanings that thick description cannot capture within a cultural setting. This paper explores how such meanings are created within a subset of the domain of photography. Using data gathered over several years, I constructed the semiotic code 'horizon' photographers use when 'in the field' for photographing periods of twilight. This code explains the relevance of subject matter to the photograph's aesthetics. Specifically, I detail how 'the horizon' communicates the potential for the photographer to 'capture' the index of a symbol that later permits the photographer culturally mark scenes with 'light'. In doing so, the paper explains how photography is a means through which a given truth about a given culture is made intelligible, elaborating the relationship between cultural meaning, narrative and decision-making despite the increased automation of the means of production of photographs. This is done to examine how this process of cultural marking is changing and why the agency of 'the photographer' still matters for evaluating the cultural significance of the resulting photograph and for photography as a vital part of ethnographic research. This paper concludes with a commentary on the aesthetics of twilight as an allegorical reflection of society.